Peran Pendamping Lokal Desa (PLD) Dalam Pembangunan Jalan Usaha Tani di Nagari Taeh Baruah Kabupaten Lima Puluh Kota - Muhammad Rohim; Hasbullah Malau (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This study analyzes the role of Village Local Facilitators (Pendamping Lokal Desa/PLD) in the development of farm roads (Jalan Usaha Tani/JUT) in Nagari Taeh Baruah, Lima Puluh Kota Regency, focusing on the stages of planning, implementation, supervision, as well as inhibiting factors and their impacts on construction quality. This research employs a qualitative descriptive approach through in-depth interviews with PLDs, the village head, sub-district facilitators, hamlet leaders, and beneficiary communities, supported by field observations and document analysis. The findings indicate that PLDs perform roles as facilitators, dynamizers, and administrative regulators; however, their effectiveness is constrained by limited technical capacity, excessive workload across multiple villages, and weak institutional coordination. These limitations contribute to discrepancies between planned and realized road construction and to suboptimal physical quality of farm roads. The study highlights the need to strengthen PLDs’ technical capacity and to establish multilayered supervision mechanisms to improve the quality of rural infrastructure development.